According to Arfken et al. Mathematical Methods p.277 $$[x,p^2]=xp^2 - pxp + pxp -p^2x =[x,p]p + p[x,p]= 2ip \, .$$ According to the text this follows solely from $[x,p]=i$.

I'm not understanding how the squared operator is being applied.

How is the commutator on squared operators supposed to work to get the middle terms $pxp$? Why would it not be $[x,p]p - p[x,p]$.


2 Answers 2


You can either think of the middle term as "adding zero" to an equality, or you can use the commutator relationship to replace $xp^2$ and $p^2 x$ with

$$xp^2 = (xp)p = (px + [x,p])p$$


$$p^2 x = p(px)= p(xp - [x,p]).$$

Using commutivity and substituting these into the original expression, you'll see the $pxp$ terms cancel:

$$xp^2 - p^2x = pxp + [x,p]p - pxp + p[x,p] = [x,p]p + p[x,p].$$

Since $[x,p]$ is a scalar, namely $i$, you can move $p$ to either side freely, and

$$[x,p]p + [x,p]p = 2[x,p]p = 2ip.$$

So you see, all we needed to prove this was the commutator $[x,p]$, and that $p$ commutes with it. You can follow a structurally identical line of reasoning to show by induction that

$$[x,p^n] = inp^{n-1}.$$


I think you're missing an $\hbar$, but it is due to the useful formula,

$$ [x, p^{n}] = i \hbar \frac{\partial}{\partial p} (p^{n})$$

for which in your case, $n = 2$.

This formula I provided above is a special case of the more general formula, (in one dimension)

$$ [x, F(p)] = i \hbar \frac{\partial}{\partial p} (F)$$

  • $\begingroup$ ah, I didn't notice that. They left off $\hbar$ and I think you left off a minus. (assuming the MIT youtube videos are the standard form). $\endgroup$ Oct 14, 2018 at 19:43
  • $\begingroup$ They made the normalization that $\hbar=1$ $\endgroup$ Oct 14, 2018 at 19:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.